Brain Aneurysms in the Pediatric Population of Slovenia: A Case Series - Ilovar, Saša; Benedik, Mirjana Perković; Vesnaver, Tina Vipotnik; Osredkar, Damjan (Neuropediatrics, 2019)
Background Brain aneurysms are rare in the pediatric population. The diagnosis of a brain aneurysm in a child may be difficult because of its infrequency and often subtle or nonspecific clinical presentation. Endovascular therapy and microsurgical treatment are increasingly used approaches in treating children, possibly contributing to favorable outcomes if patients are treated in a timely manner.Objective We were interested in the clinical presentation, symptoms, diagnostics, treatment, and follow-up of pediatric patients with brain aneurysms in Slovenia.Methods This was a retrospective review of medical documentation of children with intracranial aneurysms treated at the University Children's Hospital in Ljubljana, Slovenia, from January 1998 to December 2017.Results We identified a cohort of eight children (median age: 14.9 years; range: 2.8–17.7). The estimated incidence of pediatric brain aneurysms in Slovenia is 0.12/100,000 children per year. We observed a male predominance (1.7:1). Half of the patients presented with acute onset of neurologic symptoms and three with subarachnoid hemorrhage. One of the patients had a related stroke. The presenting symptoms were tonic–clonic seizures, hemiparesis, paresthesias, speech disturbance, and cranial nerve palsy. The other half of aneurysms were identified incidentally. Five patients had anterior circulation aneurysms; the most prevalent location was the internal carotid artery. One patient was treated with surgical procedures, four patients were treated with endovascular procedures, and three patients were treated conservatively. Outcome was excellent in all patients.Conclusion Endovascular interventions and microsurgical procedures appear to be safe and effective in the treatment of brain aneurysms in the pediatric population. Asymptomatic patients with brain aneurysms need close follow-up.
Keywords: aneurysm; brain; cerebral; children; pediatric population